The spirit of Tibetan Buddhism - Van Schaik, Sam (Sacred literature series., 2016)
"A leading writer and researcher on Tibet, Sam van Schaik offers an accessible and authoritative introduction to Tibetan Buddhism by examining its key texts, from its origins in the eighth century to teachings practiced across the world today. In addition to demonstrating its richness and historical importance, van Schaik's fresh translations of and introductions to each text provide a comprehensive overview of Tibetan Buddhism's most popular teachings and concepts--including rebirth, compassion, mindfulness, tantric deities, and the graduated path--and discusses how each is put into practice. The book unfolds chronologically, conveying a sense of this thousand-year-old tradition's progress and evolution. Under the spiritual leadership of the Dalai Lama, Tibetan Buddhism has an estimated ten to twenty million adherents worldwide. Written for those new to the topic, but also useful to seasoned Buddhist practitioners and students, this much-needed anthological introduction provides the deepest understanding of the key writings currently available."--Provided by publisher